2009
DOI: 10.1021/ic902048b
|View full text |Cite
|
Sign up to set email alerts
|

Structural Mapping and Framework Interconversions in 1D, 2D, and 3D Divalent Metal R,S-Hydroxyphosphonoacetate Hybrids

Abstract: Reactions of divalent cations (Mg(2+), Co(2+), Ni(2+), and Zn(2+)) with R,S-hydroxyphosphonoacetic acid (HPAA) in aqueous solutions (pH values ranging 1.0-4.0) yielded a range of crystalline hydrated M-HPAA hybrids. One-dimensional (1D) chain compounds were formed at room temperature whereas reactions conducted under hydrothermal conditions resulted in two-dimensional (2D) layered frameworks or, in some cases, three-dimensional (3D) networks incorporating various alkaline cations. 1D phases with compositions [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 23 publications
(30 reference statements)
2
16
0
1
Order By: Relevance
“…123 In the 1D Zn-HPAA material the Zn-O distance is 2.042(2) Å . 109 In the 1D material Ni-HPAA the Ni-O distance is 2.0322(18) Å . 124 In 3 Cl] Á 3.5py (py ¼ pyridine), 1.913(9) Å to 1.964(5) Å .…”
Section: The Metal-oxygen Bond In Metal Coordinated Phosphonatesmentioning
confidence: 99%
See 1 more Smart Citation
“…123 In the 1D Zn-HPAA material the Zn-O distance is 2.042(2) Å . 109 In the 1D material Ni-HPAA the Ni-O distance is 2.0322(18) Å . 124 In 3 Cl] Á 3.5py (py ¼ pyridine), 1.913(9) Å to 1.964(5) Å .…”
Section: The Metal-oxygen Bond In Metal Coordinated Phosphonatesmentioning
confidence: 99%
“…An identical trend is observed for the series M-HPAA materials (M ¼ Mg, Ca, Sr, Ba), as shown in Figure 14.19. 98,99,109 Bond distances versus ionic radii of the first row divalent transition metal ions are plotted in Figure 14.20. It is obvious that there is no discernible trend.…”
Section: The Metal-oxygen Bond In Metal Coordinated Phosphonatesmentioning
confidence: 99%
“…Synthesis conditions were screened by high-throughput methodology with a system previously reported [31,32]. The aluminum autoclave block contains 36 Teflon-lined reaction chambers of 5 mL volume.…”
Section: Small Scale-synthesis: High-throughput Studymentioning
confidence: 99%
“…[6][7][8][9] The materials can be used as proton conductors and for the modification of surfaces because of their polar pores and different organic groups. [10][11][12][13][14][15][16] Zirconium(IV) phenylphosphonate was one of the first described metal phosphonates. 17 Cunningham et al showed different syntheses of divalent metal phenylphosphonates with the general formula M(II)(O 3 PC 6 H 5 )•H 2 O.…”
Section: Introductionmentioning
confidence: 99%